PENGARUH IMPLEMENTASI KEBIJAKAN STANDAR PELAYANAN MINIMAL (SPM) BIDANG KESEHATAN TERHADAP EFEKTIVITAS PELAKSANAAN PROGRAM KESEHATAN DASAR PADA DINAS KESEHATAN KABUPATEN GARUT - Ikeu Kania (Indonesian Journal of Dialectics, 2011)
The background of this study originated from yet effective implementation of primary health programs in Garut District Health Office. This is indicated by the low life expectancy (AHH). This condition is thought to have successful implementation of health policy particularly in health policy implementation of SPM. The purpose of this study is to reveal the influence of SPM in health policy implementation of the effectiveness of the implementation of primary health programs.             This study used an explanatory research design using quantitative approaches and statistical analysis techniques using SEM. Technique of data collecting is done through study of documentation and field study through observation, questionnaires and interviews.The results showed that in health policy implementation of SPM significantly influence the effectiveness of basic health programs. Dimensional attitude of the implementers have the smallest value and less able to measure or reflect the implementation of the policy variables, can therefore be argued that the attitude of the implementers have not shown a good attitude. Therefore, the results of this study can be put forward a new concept that the attitude of the implementers that are less disciplined and less responsible in carrying out tasks can lead to failure of policy implementation.